Can we prevent fatal liver failure under valproate? - Schmid, Markus; Connemann, B. J.; Wolf, R. C.; Flechtenmacher, Christa; Eisenbach, Christoph; Schönfeldt-Lecuona, C. (Pharmacopsychiatry, 2010)
Valproic acid (VPA) has been used as an anticonvulsant for more than 30 years. Meanwhile, VPA has also been approved by the FDA for the treatment of bipolar disorders. We report the case of a 58-year-old female patient, who died from liver failure, probably due to treatment with VPA.